Information and communication technologies-assisted after-hours work: A systematic literature review and meta-analysis of the relationships with work–family/life management variables - Santos, Alda; Roberto, Magda Sofia; Camilo, Cláudia; Chambel, Maria José (Frontiers in Psychology, 2023)
The phenomenon of information and communication technology (ICT)-assisted after-hours work has led to rising academic interest in examining its impact on workers’ lives. ICT-assisted after-hours work may intrude the home domain and contribute to higher work–family/life conflict, lower work–family/life balance, or higher work–family/life enrichment (the last one owing to the acquisition of competencies transferable to the home domain). Additionally, owing to cultural and societal differences in gender roles, the relationships between ICT-assisted after-hours work and work–family/life management variables may differ between female and male workers. To analyze the current empirical findings, this study performed a literature review with 38 articles and a meta-analysis with 37 articles. Our findings showed that ICT-assisted after-hours work was positively related to work–family/life enrichment (r = .335, p < .001; 95% CI [0.290, 0.406]), but also to work–family/life conflict (r = .335, p < .001; 95% CI [0.290, 0.406]). However, neither gender nor pre-/post-Covid significantly affect the relationship between ICT-assisted after-hours work and work–family/life conflict. Finally, future research and implications are discussed.